Peran Interpol dalam Upaya Pemberantasan Obat-Obatan Palsu di Indonesia - Adhinugroho, M. Yudhistira; Susiatiningsih, Hermini; Farabi, Nadia (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Interpol is an international organization whose focus on transnational and international crime. One of the concerns is pharmaceutical crimes related to the distribution of counterfeit drugs. Indonesia, as the largest country in Southeast Asia, is surely cannot be separated from the cycle of counterfeit drugs distribution. This study aimed to understand the role and purpose of Interpol as international organization om combating counterfeit drugs in Indonesia. Therefore, this study used the concept of role and purpose of international organization through neoliberalism institutional perspective. This study showed that Interpol had fulfilled the expectation which was determined by the aforementioned concept. One of which is by doing Pangea Operation. It resulted that this operation has given benefits to Indonesia by creating platform for different sectors to cooperate synergistically.